ANALYSIS OF PARKING FEASIBILITY CAPACITY AT LANDUNGSARI MARKET, DAU DISTRICT, MALANG REGENCY - Rifky Aldila P.; Andy Kristafi A. (Journal Innovation of Civil Engineering (JICE), 2021)
Landungsari Market is one of the traditional markets built by the local village government to accelerate the village economy. Previously, Landungsari Market was a temporary market but with an increase in sellers who were moved from the original Merjosari market so that the local government made the Landungsari market a permanent market today. With the increasing number of seller stalls in the Landungsari market, the parking lot in the Landungsari market has decreased so that it demands the possibility of illegal parking occurs in some areas of the market. The research objective was to determine the characteristics of parking, parking feasibility, and parking solutions. The data used are primary data and secondary data. The results obtained in this study are the number of parking spaces is still less than the number of parking vehicles, namely for two-wheeled parking lots, the parking needs exceed the normal capacity, while the average motorbike parking space unit is 129 parking spaces and the average The car park space unit is 11 parking spaces, so with this condition, it is deemed inappropriate parking facilities and additional parking lots to increase the parking capacity of vehicles, especially for two-wheeled vehicles